Pricing climate-related risks in the bond market - Agliardi, Elettra; Agliardi, Rossella (Journal of Financial Stability, 2021)
We develop a model for defaultable bonds incorporating both uncertainty about corporate earnings and uncertainty due to climate-related risks, which determine downward jumps in the firm value. In particular, we study how bond pricing is affected by transition risks, such as those coming from an abrupt change of climate policies. We show how the issuer’s credit quality changes as a result of its engagement in projects funded by green bonds and study the impact of green bonds on investors’ portfolio allocation. The way ‘green’ bonds may contribute to financial stability is also discussed.